2020
DOI: 10.1111/gbb.12701
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the neuronal genome organizer and transcription factor CTCF induces neuronal death and reactive gliosis in the anterior cingulate cortex

Abstract: CCCTC‐binding factor (CTCF) is a genome organizer that regulates gene expression through transcription and chromatin structure regulation. CTCF also plays an important role during the developmental and adult stages. Cell‐specific CTCF deletion studies have shown that a reduction in CTCF expression leads to the development of distinct clinical features and cognitive disorders. Therefore, we knocked out Ctcf (CTCF cKO) in the excitatory neurons of the forebrain in a Camk2a‐Cre mouse strain to examine the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Neuronal death following sequential microgliosis and astro-gliosis was also observed in the anterior cingulate cortex (ACC) of cKO mice. Indeed, our previous study on the ACC demonstrated apoptotic cell death of cortical neurons in cKO mice over 5 months of age, subsequent to age-dependent aggravation in reactive gliosis at 4 months of age ( 15 ). However, in the present study, we found that hippocampal neuronal damage and death induced by CTCF deficiency occur later than cortical neuronal death of the ACC and we assume that it might attribute to enrichment of neurogenesis-related genes in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal death following sequential microgliosis and astro-gliosis was also observed in the anterior cingulate cortex (ACC) of cKO mice. Indeed, our previous study on the ACC demonstrated apoptotic cell death of cortical neurons in cKO mice over 5 months of age, subsequent to age-dependent aggravation in reactive gliosis at 4 months of age ( 15 ). However, in the present study, we found that hippocampal neuronal damage and death induced by CTCF deficiency occur later than cortical neuronal death of the ACC and we assume that it might attribute to enrichment of neurogenesis-related genes in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…( 7 ) and Kwak et al . ( 15 ). Littermates without the Cre transgene or the floxed Ctcf gene were used as controls (CTL).…”
Section: Methodsmentioning
confidence: 99%
“…We showed that Ctcf gene deficiency leads to altered gene expression and impaired synaptic plasticity in the forebrain of adult mice [4,6]. Moreover, recently we also showed neuroinflammation with reactive gliosis in the cortex from 16 weeks of age accompanied by neuronal cell death at over 20 weeks of age in forebrain glutamatergic neuronspecific Ctcf gene KO (CTCF cKO) mice [7].…”
mentioning
confidence: 97%
“…In this study, we showed that adult CTCF cKO mice exhibited signs of lack of behavioral flexibility and cognitive dysfunction in the PDr and dPAL touch screen test. These cognitive impairments are likely due to the loss of glutamatergic neurons in the cortex, particularly in the ACC, as inhibitory neurons in the striatum are relatively intact in adult CTCF cKO mice [7]. ACC is known to be involved in behavioral flexibility as well as decision making, adaptation, and anticipation in rodents [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation